Preparation and Characterization of Some Polymer/Pharmaceutical-Based Composites. Part. Ii Ivermectin - Rabagliati-Canessa, F; Cardenas-Sankan, G; Orihuela-Diaz, P; Galvez-Manriquez, D; Zapata-Ramirez, P; Canales-Arévalo, D; Saavedra-Gonzalez, M (Springer Verlag, 2018)
Composites of low-density polyethylene, LDPE, poly(ethylene-co-vinyl acetate), EVA, and LDPE/EVA 70/30 and 50/50% (weight) blend plus ivermectin (1 and 3% weight) were prepared through the melt-blending process. Ivermectin resulted homogenously dispersed in polymer matrices. The polymer/ivermectin composites showed thermal behavior similar to those of the original polymer matrices. Ivermectin release from the composites, was examined in vitro for various lengths of time and their release percentages were determined by photometric UV spectroscopy and their release percentages reported. The prolonged release of the drug indicates that ivermectin-loaded film offer potential application to control inflammatory events and also antiparasitic properties. © 2017, Springer-Verlag Berlin Heidelberg.